Causes and Consequences of Corporate Assets Exchange by China’s Listed Companies - WANG, Jiwei (Institutional Knowledge at Singapore Management University, 2010)
China’s listed companies often exchange corporate assets with their unlisted affiliates such as parent companies, which is rarely observed in their American counterparts. We find that listed companies which are incompletely restructured from former state-owned enterprises tend to exchange more profitable assets for less profitable assets (i.e., tunneling). However, when there is a need to avoid reporting losses and to raise additional capital, listed companies tend to exchange less profitable assets for more profitable assets (i.e., propping). We also find that the market reacts indifferently to assets exchange announcement. Finally, we find that assets exchange with tunneling (propping) incentive is associated with detrimental (improved) post-exchange stock performance and financial performance. In summary, this study contributes to the corporate assets literature by providing two new incentives (tunneling and propping).